Cultural Approach to Election Conflict Resolution in South Buru District, Province of Maluku - Anwar Alaydrus; Mohammad Jafar Loilatu; Zuly Qodir; Amera Mahfin; Paisal Akbar (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
This paper aims to analyze conflict resolution in South Buru during the regional election through a cultural approach. The conflict in the South Buru Regency was caused by dissatisfaction with the election results. This study uses qualitative tool analysis by choosing Nvivo as a computer assistant program to answer the question; the data in this study were sourced from direct observation and interviews during the conflict resolution process, and informants were selected based on the representation of each group. This analysis shows that the conflict in regional elections is caused by two dominant factors, namely the traditional doctrine of indigenous peoples. Meanwhile, the approach used in resolving regional election conflicts is an accommodation approach and a local wisdom approach. This study classifies that traditional communities in resolving conflicts tend to use a traditional approach, even though the category of conflict is not a cultural conflict. Exploring this conflict approach, Nvivo proves this by showing a correlation between the conflict approach and the conflict caused.